2010
DOI: 10.1159/000273074
|View full text |Cite
|
Sign up to set email alerts
|

Is Repair of Incisional Hernias by Polypropylene Mesh a Safe Procedure?

Abstract: Objective: The aim of our study was to evaluate the safety of the intraperitoneal mesh repair procedure and to assess the complications that develop after the procedure. Subjects and Methods: We reviewed the records of 25 patients who underwent intraperitoneal mesh repair procedures. Data on age, sex, size and cause of the hernia, postoperative mortality, and morbidity with special attention to complications were obtained from the medical records. Results: Of the 25 patients (7 males, 18 females), the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…of working days lost, cost of antibiotics and drugs etc. [3] Among the mesh used in laparoscopic repair, similar to others [4,5], we found no difference in outcomes, complications and recurrence with either simple polypropylene or composite PROCEED mesh. Hence, to bring down the cost in our setup, polypropylene mesh can be used in laparoscopic ventral hernia repair.…”
Section: IVsupporting
confidence: 78%
“…of working days lost, cost of antibiotics and drugs etc. [3] Among the mesh used in laparoscopic repair, similar to others [4,5], we found no difference in outcomes, complications and recurrence with either simple polypropylene or composite PROCEED mesh. Hence, to bring down the cost in our setup, polypropylene mesh can be used in laparoscopic ventral hernia repair.…”
Section: IVsupporting
confidence: 78%
“…The available literature data reported the incidence of infection and bleeding of 10% 23 . Our study results correlate well with other studies, where the percentage of early minor complications (seroma, hematoma, infection) ranged from 16% to 18%, and severe complications from 6% to 27% (intestinal obstruction, intraperitoneal infection and enterocutaneous fistula), accordingly 6,20 . Kingsnorth et al 19 in their study reported the early complications rate of 34%.…”
Section: Discussionsupporting
confidence: 92%
“…Enterocutaneous fistula is rarely formed with synthetic mesh placed extraperitoneally 27 , although some authors reported increased incidence of complications with intraperitoneally placed mesh 6,25,28,29 . In this study, enterocutaneous fistula was observed in one patient with synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation